MORPHOMETRIC COMPARISON OF SEAGRASS ENHALUS ACOROIDES AT TUKAK BEACH AND TANJUNG KERASAK BEACH SOUTH BANGKA REGENCY - Ramadhayanti, Rizka; Umroh, Umroh; Utami, Eva (Jurnal Perikanan Unram, 2025)
Variations in water quality and substrate characteristics between Tukak Beach and Tanjung Kerasak Beach are presumed to influence the morphometric traits of Enhalus acoroides growing in these areas. Based on previous studies, there is a need for more comprehensive investigation in the South Bangka region, particularly focusing on Tukak Beach and Tanjung Kerasak Beach as the main study sites. This research aims to identify morphometric differences in Enhalus acoroides between the two locations, as well as to analyze the relationship between these morphological characteristics and the respective water quality parameters. The fieldwork was conducted in January 2024, with sampling carried out at Tukak Beach and Tanjung Kerasak Beach. Data were collected from six sampling stations, yielding a total of 360 morphometric samples of Enhalus acoroides. The results revealed notable differences in morphological measurements of Enhalus acoroides between the two study areas. At Tukak Beach, analysis of water quality indicated a significant correlation between dissolved oxygen (DO) levels and leaf length of Enhalus acoroides. Meanwhile, findings from Tanjung Kerasak Beach suggested that the local water quality exhibited a moderate level of correlation with the morphometric traits of the same species